Use of foot snares to capture large felids. Issue 2 (9th November 2020) - de Araujo, Gediendson Ribeiro; de Deco‐Souza, Thyara; Morato, Ronaldo Gonçalves; Crawshaw, Peter G.; da Silva, Leanes Cruz; Jorge‐Neto, Pedro Nacib; Csermak‐Jr, Antônio Carlos; Bergo, Letícia C. F.; Kantek, Daniel Luis Zanella; Miyazaki, Selma Samiko; Beisiegel, Beatriz de Mello; Tortato, Fernando Rodrigo; et al.
Abstract: The study of free‐living felids requires the capture of individuals from the wild to collect biological samples and to equip them with GPS‐satellite collars for telemetry monitoring. The traditional methods used by researchers to capture wild felids are box traps and trained hounds, both of which have disadvantages. We present the description of the foot snare and the adaptations required for the capture of jaguars and cougars, showing its efficiency. The foot snare consists of a combination of structures. It is composed of a thrower system, which is responsible for closing the steel cable noose on the paw of the animal; a holding system, which is responsible for securing the animal safely, after stepping into the trap; and a monitoring system, consisting of a VHF transmitter that allows remote monitoring of the snares. The snares are set on trails and roads according to the presence of tracks, scats and other evidence indicating use by the two species of large felids or as determined by monitoring camera traps. Thirty jaguars (16 females and 14 males) and six cougars (all males) were captured. Three jaguars in the Pantanal were captured more than once, therefore totalling 34 capture events. Snares have been demonstrated to be a safe and efficient method to capture these felids. Resumo: O estudo de felídeos selvagens de vida livre requer a captura de indivíduos da natureza para colher amostras biológicas e equipá‐los com colares com GPS para monitoramento por telemetria. Os métodos tradicionais utilizados pelos pesquisadores para capturar felídeos selvagens são armadilhas de gaiolas e cães treinados, ambos apresentando desvantagens. Apresentamos a descrição da técnica de laço e as adaptações necessárias para a captura de onçaspintadas e onças‐pardas, comprovando sua eficiência. O laço consiste em uma combinação de estruturas. É composto por um sistema de gatilho, responsável por fechar o laço do cabo de aço na pata do animal; um sistema de contenção, responsável por proteger o animal com segurança, depois de entrar na armadilha; e um sistema de monitoramento, consistindo em um transmissor VHF que permite o monitoramento remoto das armadilhas. As armadilhas são colocadas em trilhas e estradas de acordo com a presença de trilhas, arranhados e outras evidências indicando o uso pelas duas espécies de felídeos grandes, ou conforme determinado pelo monitoramento das armadilhas fotográficas. Trinta onças‐pintadas (16 fêmeas e 14 machos) e seis onças‐pardas (todos machos) foram capturados. Três onças‐pintadas no Pantanal foram capturadas mais de uma vez, totalizando 34 eventos de captura. As armadilhas provaram ser um método seguro e eficiente para capturar estes felídeos.